(3TQM eLeY GdHMQjf hedJbi GdfgQjfs - (3eLghds ((3YHO GdQMef Hf YeQ Hf CMeO GdUaj GdbhGSs)
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH GdfcGM (B: (3ojSf GdGYJOGd hjLH aj hGdfcGM GdhWA (B( (3cPG (B) (3hbO jchf GdYbO Hbhd (B: (3fcMJgG hfcMJ EPG JRhLJ hgj fGcM aj Hfj adGf Cj gj (B- (3gcPG PcQg UGMH GdUMGM hgcPG gh aj GdTQY aEfg jWdb hjQGO Hg GdhWA (B( (3cPG (B) (3hgh MbjbI s
(3BNQgG (B:s
(3aEf de jJMbb EYQGHgG hfbWgG hCgedJ hbY GdTc ddfGXQ ajgG hEf CYQHJ Ydi NdGa eG jSJMbg hbY GdZdW hdgPG NU Pdc HGdhUjI aEfgG ehVY GdGMJjGW hgPG gh GdPj gOGfj Ydi hVY GdQbhe aEfgG bQGjf JOd Ydi Jdc GdChVGY Ydi eG SHb HjGfg aj UOQ GdcJGH s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3Gdabg GdMfHdjs